Two decades of depopulation in Serbia 2002–2022 - Marinković, Ivan (Sociološki pregled, 2023)
The main characteristic of the population changes in Serbia since the beginning of the 21st century is increasingly pronounced depopulation. The difference in the number of births and deaths is continuously increasing to the detriment of births, and emigration traditionally exceeds immigration during the entire analyzed period 2002-2022. The problem in the analysis of population dynamics in Serbia is the lack of methodological consistency in the results of population censuses, so the main goal of this paper is the methodological harmonization of census data to see as realistically as possible the population changes in the period of the last three censuses in 2002, 2011 and 2022. Overall, the depopulation in Serbia is by about 135,000 higher in the period 2002-2022, if we correct the officially published data, while the importance of the negative net migration in the total population changes has increased to over 20%. Population decline is present in as many as 95% of the settlements in Serbia.